Project Management Education in Chemical Companies in the Czech Republic - Košťálová, Jana; Bednaříková, Marie (STEF92 Technology Ltd., 2016)
Companies have to implement a lot of changes to assure competitiveness and further development. More extensive changes are usually implemented in a way of projects. It is suitable to use findings of the project management theory to manage projects in a successful way. The level of project management is affected with many factors. Range of knowledge and skills of project managers and members of project teams and also general awareness about company project management in case of the company management as well as in case of its skeleton staff can be counted among the important factors. It is possible to increase this knowledge and skills using a long-term and goal-directed education of staff. There are many ways and instruments to be used for the education of employees. The article is concentrated on evaluation of project management education in some selected chemical companies in the Czech Republic. There was explored an interest to arrange project management education and the attitude to arranging it in these companies. In the final part of the article there are some recommendations following from the research for companies in chemical industry as far as project managers and members of project teams and project management education generally speaking is concerned.
Vzdělávání v oblasti projektového řízení v podnicích chemického průmyslu v České republice
Keywords: project management; project management education; project management information systems; chemical industry; projektové řízení; vzdělávání v oblasti projektového řízení; informační systémy na podporu projektového řízení; chemický průmysl